A mechanism based on independent modeling for split-shaft gas turbines participating in power spot market - LIN Sunben; TANG Qiwen; XU Lizhong; ZHAO Yiyan (Zhejiang dianli, 2022)
Large-scale integration of new energy presents higher demands on power system regulation capacity. In order to give full play to the regulation function of split shaft gas-steam combined cycle units， it is urgent to explore and establish a safe， reliable， and stable power spot market participation mechanism. Firstly， the characteristics and applicability of different market mechanisms for split-shaft gas turbines at home and abroad are compared and analyzed. Secondly， a mechanism based on independent modeling for split-shaft gas turbines participating in power spot market according to the experience of power market construction in Zhejiang province is introduced in detail. The split-shaft gas turbines are modeled separately， and steam turbine output is determined by the gas turbine output， which puts an end to the dependence relationship between the gas turbines and steam turbines. The gas turbine bid is incorporated into the objective function， and the ratio of gas turbine and steam turbine output is incorporated into the constraint conditions， which solves the problem of the variable operation mode of split-shaft gas turbines. Then the measured data of Zhejiang spot market is analyzed to verify the rationality of the model design， control， and income index results. Finally， experience is summarized and provided for diversified generation entities to participate in mechanism design in the spot market.